2008
DOI: 10.1128/aac.00661-08
|View full text |Cite
|
Sign up to set email alerts
|

RamA Confers Multidrug Resistance in Salmonella enterica via Increased Expression of acrB , Which Is Inhibited by Chlorpromazine

Abstract: Salmonella enterica serovar Typhimurium SL1344, in which efflux pump genes (acrB, acrD, acrF, tolC) or regulatory genes thereof (marA, soxS, ramA) were inactivated, was grown in the presence of 240 antimicrobial and nonantimicrobial agents in the Biolog Phenotype MicroArray. Mutants lacking tolC, acrB, and ramA grew significantly worse than other mutants in the presence of 48 agents (some of which have not previously been identified as substrates of AcrAB-TolC) and particularly poorly in the presence of phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 36 publications
5
113
1
3
Order By: Relevance
“…The regulation of the acrAB genes has been studied extensively in human-pathogenic enterobacteria. Several members of the AraC/XylS family, including MarA, RamA, Rob, and SoxS, have been identified as positive transcriptional regulators of this efflux system (10,13,14,21,54,58). In this study, we identified four regulators from the plant pathogen E. amylovora that are closely related to the MarA/Rob/ SoxS group of AraC/XylS transcriptional activators from E. coli (see Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The regulation of the acrAB genes has been studied extensively in human-pathogenic enterobacteria. Several members of the AraC/XylS family, including MarA, RamA, Rob, and SoxS, have been identified as positive transcriptional regulators of this efflux system (10,13,14,21,54,58). In this study, we identified four regulators from the plant pathogen E. amylovora that are closely related to the MarA/Rob/ SoxS group of AraC/XylS transcriptional activators from E. coli (see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that high-level expression of AraC/XylS regulators is required to induce antibiotic resistance in enteric bacteria (52)(53)(54). Therefore, we generated high-copynumber plasmids overexpressing the pliA, rob, soxS, and opiA genes from their native promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have studied the important roles of AcrAB in bacterial drug resistance and virulence; however, the regulation mechanism of acrAB in Salmonella in response to extracellular signals has not been well characterized. AcrAB regulation is mediated by five regulators: MarA, SoxS, Rob, AcrR and RamA (Bailey et al, 2008;Ma et al, 1996;Randall & Woodward, 2002;Rosenberg et al, 2003;Schneiders et al, 2003). In Salmonella, AcrAB regulation in response to indole, bile salts and E. coli metabolites depends on RamA (Nikaido et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, AcrAB is regulated by three activators, MarA, SoxS and Rob, and one repressor, AcrR (Ma et al, 1996;Randall & Woodward, 2002;Rosenberg et al, 2003). In Salmonella, RamA is involved in inducing acrAB in addition to the (Bailey et al,2008 ;Schneiders et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of furan compounds (such as furfural) is an unavoidable consequence of the use of relatively high temperatures (>140ºC) to break LCM into fermentable sugars (Tomás-Pejó et al, 2010). Additionally, the higher temperature steam explosion methods (220ºC) may generate up to 8 mM furfural (Bailey et al, 2008). This can significantly reduce the ethanol yields achieved or reduce the volumetric productivity (the ethanol output per unit time) thus reducing the process efficiency.…”
Section: Metabolic Profiling Of Yeast Cultured In Pre-treatment Genermentioning
confidence: 99%